Burnout and psychological distress amongst Australian healthcare workers during the COVID-19 pandemic. (February 2021) - Dobson, Hannah; Malpas, Charles B; Burrell, Aidan JC; Gurvich, Caroline; Chen, Leo; Kulkarni, Jayashri; Winton-Brown, Toby
Objective: To examine psychological distress in healthcare workers (HCWs) during the COVID-19 pandemic in April–May 2020. Methods: A cross-sectional survey examining demographic, employment and mental health characteristics of HCWs in a large metropolitan hospital in Australia. Results: HCWs showed significant symptoms of moderate-severe level depression (21%), anxiety (20%) and posttraumatic stress disorder (PTSD; 29%), associated with burnout, prior psychiatric history, profession and resilience. Conclusion: Despite low levels of COVID contact, moderate to high levels of psychological distress were reported. Continued monitoring and support for HCWs' mental well-being is warranted as the COVID-19 pandemic develops.